2015
DOI: 10.1080/14735903.2015.1071547
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fixation during decomposition of sugarcane (Saccharum officinarum) is an important contribution to nutrient supply in traditional dryland agricultural systems of Hawai'i

Abstract: Nitrogen (N) is unique among essential elements required for life, in that it must be fixed from the vast atmospheric reservoir before most organisms can use it. Prior to industrial nitrogen fixation, many agricultural systems were limited in their productivity by N. What sustained N in the ancient Hawaiian dryland (rain-fed) agricultural systems that lacked legumes or other known significant N inputs? N-fixation during sugarcane (Saccharum officinarum) growth and litter decomposition was examined in settings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 35 publications
2
35
0
Order By: Relevance
“…The average population increases by a factor of 6.6 entirely as a result of a 4.2-times increase in the N-fixation rate. At this point we do not have evidence that points clearly to one end of the N-fixation spectrum or the other, although we do know that varieties of sugar cane associated with nitrogen fixation during decomposition were cultivated on Rapa Nui, as in Hawai'i, where the estimates originated (Lincoln and Vitousek, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The average population increases by a factor of 6.6 entirely as a result of a 4.2-times increase in the N-fixation rate. At this point we do not have evidence that points clearly to one end of the N-fixation spectrum or the other, although we do know that varieties of sugar cane associated with nitrogen fixation during decomposition were cultivated on Rapa Nui, as in Hawai'i, where the estimates originated (Lincoln and Vitousek, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…What N is available in Polynesian agricultural systems that lack a symbiotic N fixer comes primarily from two sources: dissolved N in rainfall and from the fixation of nitrogen from the atmosphere by the microbial community as it decomposes sugarcane and other plants (Lincoln and Vitousek, 2016). The deposition rate of dissolved mineral N has been measured in some places and estimated for others across the globe, but the remote Pacific remains under studied in this regard.…”
Section: Other Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In situ field management that increases capture and storage of soil moisture, minimizes moisture loss, and extends periods of sufficient moisture would extend the growing season and increase staple root crop yields. Mulching with organic material was an important practice in all the systems for both moisture conservation and nutrient inputs (e.g., Lee et al 2006, Lincoln andVitousek 2016). Rock mulches, too, likely improved ʻuala yields (see Marshall et al 2017) by reducing evaporation of soil moisture (Allen 2004, Graf et al 2008) and improving soil nutrient availability, as is suggested from work in Rapa Nui .…”
Section: Variations In Infrastructurementioning
confidence: 99%
“…Hence, relationship between microbial biomass in soil and effectiveness of management on agricultural production will aid in further understanding and possibly manipulation of nutrient flow on a terrestrial scale (McGill and Myers, 1987;Lincoln and Vitousek, 2016). Microbial biomass in agricultural soil is affectted by crop rotation (McGill et al, 1986), tillage (Carter and Rennie, 1982;Lynch and Panting, 1980a, b), soil texture (van Veen et al, 1987) and alternation of moist and dry conditions (Bottner, 1985).…”
Section: Introductionmentioning
confidence: 99%